Laboratory evaluation of Rediset modified bitumen based on rheology and adhesion properties - Zhang, Jizhe; Airey, Gordon; Grenfell, James; Yao, Zhanyong (Elsevier, 2017)
Warm mix asphalt (WMA) could significantly reduce the production temperature of asphalt mixtures. Lower production temperature meaning reduced fossil fuel consumption and greenhouse gas emission which in turn avoid environmental pollution in the road construction process. This study aims to characterise the properties of bitumen with the addition of a type of WMA additive – Rediset. The influence of Rediset on bitumen surface energy was evaluated by using the Dynamic Contact Angle (DCA) test. Complex modulus and phase angle of bitumen were evaluated through frequency sweep test using Dynamic Shear Rheometer (DSR). The high-temperature viscosity of bitumen was measured using a corn and plate system which installed in the DSR equipment. Finally, the Pneumatic Adhesion Tensile Testing Instrument (PATTI) test was performed to measure the tensile strength and moisture susceptibility of aggregate-bitumen combinations. The results show that the Rediset reduces the surface energy of bitumen. Moreover, as seen in the DSR test, the complex modulus increased while the phase angle decreased at the low frequency range due to the addition of Rediset. The decreased bitumen viscosity because of the addition of Rediset demonstrating reduced mixing and compaction temperature of asphalt mixture. In addition, the addition of Rediset could improve the bonding strength of aggregate-bitumen combinations at medium and high service temperatures but has no influence at low temperature. Furthermore, the Rediset is able to increase the retained tensile strength which in turn reduces the moisture susceptibility of asphalt mixture.